A review on recycling techniques for bioethanol production from lignocellulosic biomass. (October 2021) - Chen, Jiaxin; Zhang, Biying; Luo, Lingli; Zhang, Fan; Yi, Yanglei; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Wang, Xin; Lü, Xin
Abstract: Bioethanol is a promising substitute for fossil fuels to alleviate the energy crisis. To improve the economic and environmental efficiency of bioethanol production from lignocellulosic biomass, the recycling techniques related to pretreatment, enzymatic hydrolysis, fermentation and distillation are discussed in the present study. The core of recycling technique is to recycle wastes and high-cost additives, including pretreatment waste liquor, stillage, solid residues after hydrolysis and fermentation, cellulases and yeast. On the one hand, the waste liquor can be reused as fresh water for the same or different conversion steps; on the other hand, wastes are the potential feedstocks for by-products production. As for high-cost additives, the most common approach is collecting for the next batch conversion. After adoption of recycling techniques, the consumption of water, chemicals, cellulases and yeast is reduced, which directly saves the conversion cost of lignocellulosic bioethanol. Meanwhile, high-value by-products and reduction of waste disposal indirectly increase economic and environmental efficiency. Besides, this review also provides the categories of wastes, influence factors of recycling, and the advantages and disadvantages of various recycling techniques. In order to resolve the drawbacks of toxics accumulation, low recycling efficiency and low economic feasibility in the existing recycling techniques, a novel recycling strategy that meets all-components utilization, non-wastes generation and high-cost additives recycling simultaneously is proposed. Moreover, the economic and environmental evaluation of recycling techniques on a pilot or industrial scale should be made more efforts in the future. Highlights: The core of recycling technique is to reuse wastes and high-cost additives. Toxics accumulation, low recycling efficiency and economic feasibility impede recycling techniques. Integrated recycling techniques can improve the economic and environmental performance of bioethanol production. A novel integration concept of recycling technique is proposed.